2018
DOI: 10.2147/ijwh.s161840
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effectiveness of crisis counseling and psychoeducation in relation to improving mental well-being, quality of life and treatment compliance of breast cancer patients in Qatar

Abstract: BackgroundAn insufficient number of studies have been carried out in the Middle East to evaluate the role of structured psychotherapeutic interventions in enhancing breast cancer patients’ psychological well-being, quality of life and treatment compliance. This study has been designed to address this limitation by exploring the benefit of two structured psychotherapeutic interventions, crisis counseling and psychoeducation, in enhancing breast cancer patients’ psychological well-being, quality of life and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
(33 reference statements)
0
5
0
1
Order By: Relevance
“…Crisis counseling is a specific type of psychological counseling that provides psychological support and assistance to a healthy but emotionally, intellectually and physically exhausted person in difficult, challengingcircumstances. Al-Sulaiman et al, (2018), in an empirical study of crisis situations in women with high anxiety and depression confirmed a positive impact of crisis counseling and psychoeducation on them.…”
Section: Psychological Counseling Of Clients In Crisis Situationsmentioning
confidence: 69%
“…Crisis counseling is a specific type of psychological counseling that provides psychological support and assistance to a healthy but emotionally, intellectually and physically exhausted person in difficult, challengingcircumstances. Al-Sulaiman et al, (2018), in an empirical study of crisis situations in women with high anxiety and depression confirmed a positive impact of crisis counseling and psychoeducation on them.…”
Section: Psychological Counseling Of Clients In Crisis Situationsmentioning
confidence: 69%
“…Among the different therapies and techniques used, counseling emerges in the aforementioned study as a technique, derived from humanistic therapy (as with the HR is), capable of diminishing the previously mentioned negative emotions. In contrast, Al‐Sulaiman et al 35 conducted a study that aimed to understand the benefit of structured psychotherapeutic interventions, such as counseling and psychoeducation, in improving well‐being and adherence to treatment in people with breast cancer. It is specified that individuals who receive counseling—a technique that, just like the HR, belongs in the domain of humanistic therapy—show improvements in their well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that psychological support to augment medical treatment may be effective, even with this group. In fact, beneficial impacts of psychological support have been found for some conditions ( Komesu et al, 2011 ; Al-Sulaiman et al, 2018 ; Zanello et al, 2020 ), including pelvic pain ( Carty et al, 2019 ). While these data are encouraging, evidence is sparse regarding how and where such support impacts compliance (and, hence, added healthcare costs) at each point on the treatment path.…”
Section: Treating Noncompliancementioning
confidence: 99%